2011
DOI: 10.1007/s00427-011-0365-5
|View full text |Cite
|
Sign up to set email alerts
|

Complicated evolution of the caprellid (Crustacea: Malacostraca: Peracarida: Amphipoda) body plan, reacquisition or multiple losses of the thoracic limbs and pleons

Abstract: The Caprellidea (Crustacea) have undergone an interesting morphological evolution from their ancestral gammarid-like form. Although most caprellid families have markedly reduced third and fourth pereopods (the walking thoracic limbs) and pleons (the posterior body parts), one family, Caprogammaridae, has developed pleon with swimming appendages (pleopods), whereas another family, Phtisicidae, possesses well-developed functional third and fourth pereopods. The unique character status of these families implies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Like their study, the present work also shows a primarily phronimid-phrosinid clade and a vibiliid-cyllopodid clade. Another example, the good conformity between the results of a morphological study ) and a molecular study (Ito et al 2011) in the case of the caprellid amphipods, was described earlier in this paper.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Like their study, the present work also shows a primarily phronimid-phrosinid clade and a vibiliid-cyllopodid clade. Another example, the good conformity between the results of a morphological study ) and a molecular study (Ito et al 2011) in the case of the caprellid amphipods, was described earlier in this paper.…”
Section: Discussionsupporting
confidence: 81%
“…reduced the suborder Caprellidea to the status of a superfamily within the suborder Corophiidea based on a morphological cladistic study. Later, Ito et al (2011) came to the same conclusion based on molecular studies. When morphological and molecular results coincide, it increases the confidence in the hypothesis.…”
Section: Introductionmentioning
confidence: 65%
“…The phylogenetic relationships between Caprellidea are poorly understood, making the selection of an appropriate outgroup difficult. Recent molecular analyses carried out by Ito et al (2011) based on the 18S gene have indicated that a close relationship between Cyamidae (another family belonging to suborder Caprellidea) and Caprellidae exists. Thus, the COI gene sequence from one Cyamidae species, Cyamus ovalis Roussel de Vauz eme, 1834, obtained from GenBank (accession no.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…The phylogenetic relationships among Caprellidea are poorly understood, making the selection of an appropriate outgroup difficult. However, recent molecular analyses carried out by Ito et al (2011) Haplotype genealogy was also investigated by building a network of haplotypes using TCS version 1.21 (Clement et al 2000) with a 90 % statistical parsimony connection limit. All sequences were deposited in GenBank (accession numbers: JX988531-JX988603).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%